Jugular foramen tumour resulting in hypoglossal denervation pseudohypertrophy: a rare and significant cause for tongue asymmetry. Issue 1 (January 2019) - Tocaciu, S.; Irons, S.M.; McMillan, B.
Abstract: Paragangliomas of the jugular foramen are rare. They may present with symptoms of compression of the glossopharyngeal or vagus nerves, or due to secretion of catecholamines from chromaffin cells within the tumour. This case describes a rare presentation of glomus tumour. A 67-year-old patient presented with a 2-month history of right-sided tongue swelling. She was found to have an obvious swelling on the right side of the tongue but no obvious weakness or fasciculation on initial examination. Ultrasound confirmed diffuse muscle swelling, but no lesion within the tongue. Magnetic resonance imaging of the neck revealed an ipsilateral glomus jugulare tumour that extended to the hypoglossal canal, and had resulted in ipsilateral denervation pseudohypertrophy of the lingual muscles. This paper reviews presentation of glomus jugulare tumours and contributes a novel presentation of a rare entity.